The preferential treatment of green bonds - Francesco Giovanardi; Matthias Kaldorf; Lucas Radke; Florian Wicknig (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We study the preferential treatment of green bonds in the Central Bank collateral framework as an environmental policy instrument. We propose a macroeconomic model with environmental and financial frictions, in which green and conventional entrepreneurs issue defaultable bonds to banks that use them as collateral. Collateral policy solves a financial stability trade-off between increasing bond issuance and subsidizing entrepreneur default risk. In a calibration to the Euro Area, optimal collateral policy features substantial preferential treatment, implying a green-conventional bond spread of 73bp. This increases the green bond share by 0.69 percentage points, while the green capital share increases by 0.32 percentage points, which in turn reduces pollution. The limited response of green investment is caused by higher risk taking of green entrepreneurs. When optimal Pigouvian taxation is available, collateral policy does not feature preferential treatment, but still improves welfare by addressing adverse effects of taxation on financial stability.
Keywords: E44; E58; E63; Q58; 330; Green Investment; Central Bank Policy; Collateral Framework; Corporate Default Risk; Environmental Policy